As praças públicas de Natal/RN no âmbito dos problemas socioambientais urbanos - Gomes, Maria Rosângela (2012)
This paper presents the public square as a subsystem of the city for the potential integration of elements 'natural' and built environment. But sometimes the suitability of projects and the social processes involved are not compatible and favorable to their real functions in urban space. The city of Natal, with a population of 803,739 inhabitants has 253 public parks not uniformly distributed in the urban area, but mostly in central areas and their absence in some peripheral neighborhoods. In this sense, the objective of this paper is to analyze the quality and spatiality of the city's public squares within the urban socio-environmental problems. For this, use of simple random sampling to define the sample and the proportional allocation of districts, totaling 168 squares to be raised. We prepared a form to collect data on the field that includes aspects of leisure, infrastructure and environment. For each square sampled was calculated Square Quality Index (PQI), then calculating the average per IQP neighborhood. The rates found were crossed with census data and Municipal Public Administration by neighborhood, using multivariate analysis. We generated maps, charts and tables, considered appropriate to each question format, focused comparison. The public square appears as an indicator of environmental challenges present in intra-urban spaces of the city. Their spatial distribution is not consistent demand population, both by disposition and by how much. In terms of quality are characterized by different levels of inadequacy and degradation aspects of leisure, environmental and infrastructure, often causing disfigurement, abandonment and improper occupation in such spaces. Multivariate analysis point to a central concentration and their problems in certain administrative units, not only as regards the public squares, but also to aspects of education, income, and other violence, perpetuating the problem. The various levels of inadequacy and degradation of public squares have been more blatant in the poorest neighborhoods of the city, pointing to a structural pattern associated with the intrinsic characteristics of the neighborhood and the socioeconomic profile of the local population. These are problems of social and environmental dimensions, threaded in and influenced the political, economic and broader social process of transformation of the city and the urban. Based on an uneven process in which space necessarily reflect the contradictions inherent in the active forces and interests. Thus evidencing the importance of managing the necessary public effectively engaged with the problems that are present there, in order to equate them, without being prioritized certain areas of the city at the expense of others